TELEMEDICINE PAYMENT SYSTEM BASED ON QUALITY:A SCOPING REVIEW - Fatma, Zuhaira Husna; Nugraha, Ryan Rachmad (UI Scholars Hub, 2022)
Telemedicine has been proven to improve access to care. However, it is still not sure how a payment system can accommodate high-quality telemedicine services. This paper aims to study the available payment system to accommodate telemedicine with a focus on health services quality. We conducted a scoping review of the telemedicine payment system and telemedicine quality through the PubMed and CINAHL databases including primary research, literature reviews, and expert opinion, aside from policy documents. The number of records identified through the database was 286. In addition, 195 were screened after removing duplicates, and 28 papers were included in the review after meeting the inclusion criteria. From a close look, it is concluded that, in its vast options of care, telemedicine practice can be tailored to payment systems that can be accommodated to quality. According to our review, the type of payment model used to fund telemedicine services could either bolster or hinder quality improvement, depending on the setting. Furthermore, concerns such as lack of standard reimbursement policy and privacy concerns need to be mitigated early to accommodate the integration of telemedicine into the existing payment system.